Clinical scores for prediction of acute appendicitis in children in a hospital of Lima, Perú - Guzmán, Edson (2014)
Objective: To determine the usefulness of the Alvarado score and the Pediatric Appendicitis score (PAS) in the Pediatric Emergency of the National Hospital Daniel A. Carrion. Materials and methods: A prospective observational study was carried out of patients younger than 15 years of age with abdominal pain and suspected acute appendicitis (AA) attending the Pediatric Emergency in a Hospital of Lima, Peru. These patients underwent a survey to assess the parameters of the Alvarado score and PAS. Results: Three hundred and seventeen patients with abdominal pain and suspected of AA were recruited over a study period of 12 months. Of the patients, 232 were considered to have AA clinically and underwent surgery. 85.3% were confirmed by pathology and 14.7% were normal. The mean Alvarado score was 8.27±1.31; the mean Surgical Procedure Assessment (SPA) score was 8.08±1.47. Sensitivity and specificity for both scores are equivalent. The area under the curve for the Alvarado score and SPA were 0.887 and 0.901, respectively. Alvarado score higher than 6 had a sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy of 88.9, 75.6, 97.4, 68.1, and 86.4%, respectively. SPA higher than 6 points had sensitivity, specificity, PPV, NPV, and accuracy of 84.3, 80.7, 94.7, 73.1, and 86.7%, respectively. Conclusion: Alvarado score and the PAS are scores with high sensitivity, specificity, PPV, and accuracy for the diagnosis of AA when the score is higher than 6 points. The results found in our study justify their use in emergency services, but they should not be used as the only means of clinically determining the need for surgery.